Illiquidity and under-valuation of firms - Douglas Gale; Piero Gottardi (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study a competitive model in which market incompleteness implies that debt-financed firms may default in some states of nature and default may lead to the sale of the firms' assets at fire sale prices when markets are illiquid. This incompleteness is the only friction in the model and the only cost of default. The anticipation of such losses alone may distort firms' investment decisions. We characterize the conditions under which fire sales occur in equilibrium and their consequences on firms' investment decisions. We also show that endogenous financial crises may arise in this environment, with asset prices collapsing as a result of pure self-fulfilling beliefs. Finally, we examine alternative interventions to restore the efficiency of equilibria.
Keywords: D50; D80; G10; G33; 330; illiquid markets; default; incomplete markets; price distortions; inefficient investment